A Structure for the Control of Geometry and Properties of a Freeform Bending Process. Issue 11 (2021) - Ismail, Ahmed; Maier, Daniel; Stebner, Sophie; Volk, Wolfram; Münstermann, Sebastian; Lohmann, Boris
Abstract: Today, in production shaping processes, the application of closed loop control is often limited to controlling the geometry. For freeform bending processes the geometric deviations are compensated by numerous experimental iterations, without regarding the mechanical properties. Especially for freeform bent parts also the internal properties are important because, e.g., the residual stresses strongly influence the downstream process steps. In this work a multivariable feedback control structure is proposed that is able to control both, the geometry of the workpiece as well as selected mechanical properties of the material.